Psychological perspectives on divine forgiveness: 3. Trait self-control is associated with well-being through seeking divine forgiveness - Maranges, Heather M.; Fincham, Frank D. (Frontiers in Psychology, 2024)
Although a majority of the world's population believes in a Higher Power and subscribes to a religion in which divine forgiveness is emphasized, little work has been done to understand individual differences associated with seeking divine forgiveness. Building on work that suggests trait self-control facilitates well-being, the current study (N = 439, undergraduate students) applies structural equation modeling (SEM) to find that believers higher (vs. lower) in trait selfcontrol are more likely to seek divine forgiveness (b = .16), and seeking divine forgiveness represents one of the pathways associated with psychological health (i.e., seeking is associated with higher well-being, b = .21, and lower distress, b = -.07). Crucially, we operationalize both positive (well-being and flourishing) and negative (depression, anxiety, stress) aspects of psychological health and control for religiosity. These results suggest that for those who believe in God, seeking divine forgiveness may be one mechanism that links individuals' self-control to good psychological health, and this is not merely an artifact of higher levels of religiosity. Limitations and future directions are discussed.Most people around the world believe in a Higher Power and subscribe to one of the world's primary religions (Pew, 2018;Rye et al., 2000;Wormald, 2015), which emphasize the importance of divine forgiveness (i.e., forgiveness by Higher Power, Supreme Being, or God).Nonetheless, the psychological science of divine forgiveness is underdeveloped relative to those of interpersonal and self-forgiveness (Fincham, 2022). The current work adds to an emerging literature on the psychological correlates of divine forgiveness (e.g., Fincham and Maranges, 2023a, 2023b) by focusing on an active decision point in the process model of divine forgiveness-seeking divine forgiveness (Fincham and May, 2023). 1 Prior work suggests that trait self-control is associated with both religiosity (McCullough and Willoughby, 2009) and psychological well-being (De Ridder et al., 2012).Experiences of divine forgiveness have also been linked to better mental health (e.g., lower levels of depression and anxiety symptomatology, and higher levels of well-being; Chen et al., 2018; Fincham and May, 2020;Krause and Ellison, 2003) and there is a growing body of research linking religiosity to flourishing and health (e.g., Abu-Raiya et al., 2016;Cohen and